Organizational Climate and Burnout: A Systematic Review of the Role of Salary, Administration, and Workplace Relationships - Anwar, Ravel; Harefa, Agusman (Entrepreneurship Faculty, Universitas Garut, 2025)
The world of work has undergone a fundamental shift, with post-pandemic phenomena such as